Hospital Safety Index and Healthcare Provider Preparedness for Disaster-Responsive Social Welfare in Lhokseumawe, Indonesia - Rahmat Hidayat Putra; Rizanna Rosemary; Cut Husna (Women, Education, and Social Welfare, 2026)
Hospitals are critical institutions for maintaining health service continuity and social welfare during disasters, particularly in hazard-prone regions where emergency care, patient safety, and community protection depend on institutional readiness. This study aimed to assess the Hospital Safety Index (HSI) and describe healthcare provider preparedness for disaster response at Metro Medical Center General Hospital, Lhokseumawe, Indonesia. A descriptive exploratory case study was conducted from 25 to 31 March 2026 involving 100 healthcare providers and hospital personnel selected through purposive sampling. Data were collected using the HSI checklist and a 42-item preparedness questionnaire covering knowledge, attitudes, and practices. HSI data were processed using the official HSI calculator, while preparedness data were analyzed descriptively using SPSS version 27. The findings showed that the hospital achieved an overall HSI score of 0.98, placing it in Category A, with high structural safety, non-structural safety, and emergency and disaster management capacity. Healthcare provider preparedness was also generally favorable, as 70% of respondents demonstrated high disaster knowledge, 61% showed very good attitudes, and 47% reported very good disaster-related practices. However, 69% of respondents had not attended disaster training, indicating a critical gap between institutional safety status and sustainable workforce preparedness. This study implies that disaster-responsive hospitals require not only safe infrastructure and emergency management systems but also continuous, inclusive, and competency-based disaster training to strengthen healthcare workforce readiness, protect vulnerable populations, and support resilient social welfare in disaster-prone communities.